Salivary Gland Activity Obscures Mandibular Metastasis of Prostate Carcinoma on 68Ga–Prostate-Specific Membrane Antigen PET. (February 2018) - Lengana, Thabo; Lawal, Ismaheel; Boshomane, Tebatso; Ololade, Kehinde; Reyneke, Florette; Kaoma, Chimbabantiu; Mokgoro, Neo; Vorster, Mariza; Sathekge, Mike
Abstract : Abstract: We report a case of a 65-year-old man with prostate cancer; his treatment history included radical prostatectomy followed by radiation therapy and subsequent androgen deprivation therapy for more than 5 years. He currently presented with a history of rising prostate-specific antigen and complained of jaw aches. 68 Ga–prostate-specific membrane antigen PET/CT study performed for suspected biochemical recurrence demonstrated vertebral lesions and lesion in his jaw. Subsequent biopsy of jaw lesion demonstrated prostate cancer metastases.